Literasi Urgensi Peran Kesehatan Lingkungan Dalam Pencegahan Demam Berdarah Pada Anak Desa Pasie Lamgarot - Yulizar, Meri; Munawarah, Intan; Winarty, Asih; Suwati, Suwati (Rengganis Jurnal Pengabdian Masyarakat, 2025)
Community service activities through Field Study and Community Service (KKN) program on the urgency of the role of environmental health in preventing dengue fever in children in Pasie Lamgarot village aim to increase understanding and awareness of the community, especially parents and communities, about the importance of maintaining environmental hygiene to prevent the development of Aedes aegypti mosquitoes that cause dengue fever. This activity is in line with the Tri Dharma of higher education and provides students with learning and working experience through community socialization activities in Pasie Lamgarot village, Ingin Jaya District, Aceh Besar Regency, Aceh Province. So that it can be utilized as a potential to develop and provide new knowledge to the community in Pasie Lamgarot Village, Ingin Jaya District, Aceh Besar Regency, Aceh Province. The target group together with KKN students accompanied by field supervisors carry out activities (KKN) together. The socialization activity carried out is the literacy of the urgency of the role of environmental health in preventing dengue fever in children in Pasie Lamgarot Village. The results of community service activities through the KKN program have increased community understanding which is expected to create a healthier environment and minimize the incidence of dengue fever in children in Pasie Lamgarot Village.